A study of trace element contamination using multivariate statistical techniques and health risk assessment in groundwater of Chhaprola Industrial Area, Gautam Buddha Nagar, Uttar Pradesh, India. (January 2017) - Kumar, Manoj; Ramanathan, AL.; Tripathi, Ritu; Farswan, Sandhya; Kumar, Devendra; Bhattacharya, Prosun
Abstract: This study is an investigation on spatio-chemical, contamination sources (using multivariate statistics), and health risk assessment arising from the consumption of groundwater contaminated with trace and toxic elements in the Chhaprola Industrial Area, Gautam Buddha Nagar, Uttar Pradesh, India. In this study 33 tubewell water samples were analyzed for 28 elements using ICP-OES. Concentration of some trace and toxic elements such as Al, As, B, Cd, Cr, Mn, Pb and U exceeded their corresponding WHO (2011) guidelines and BIS (2012) standards while the other analyzed elements remain below than those values. Background γ and β radiation levels were observed and found to be within their acceptable limits. Multivariate statistics PCA (explains 82.07 cumulative percent for total 6 of factors) and CA indicated (mixed origin) that natural and anthropogenic activities like industrial effluent and agricultural runoff are responsible for the degrading of groundwater quality in the research area. In this study area, an adult consumes 3.0 L (median value) of water therefore consuming 39, 1.94, 1461, 0.14, 11.1, 292.6, 13.6, 23.5 μg of Al, As, B, Cd, Cr, Mn, Pb and U from drinking water per day respectively. The hazard quotient (HQ) value exceeded the safe limit of 1 which for As, B, Al, Cr, Mn, Cd, Pb and U at few locations while hazard index (HI) > 5 was observed in about 30% of the samples which indicated potential health risk from these tubewells for the local population if the groundwater is consumed. Graphical abstract: Highlights: Spatio-chemical of trace and toxic elements in the groundwater of an industrial area. Comparative analysis of concentration with WHO and BIS standards for elements. Survey study on background radiation in the study area. Estimation of total daily intake and body burden from ingestion of trace elements. Health risk assessment for trace and toxic elements.